2022
DOI: 10.1002/em.22516
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional clinical study in women to investigate possible genotoxicity and hematological abnormalities related to the use of black cohosh botanical dietary supplements

Abstract: Black cohosh (BC; Actaea racemosa L.), a top‐selling botanical dietary supplement, is marketed to women primarily to ameliorate a variety of gynecological symptoms. Due to widespread usage, limited safety information, and sporadic reports of hepatotoxicity, the Division of the National Toxicology Program (DNTP) initially evaluated BC extract in female rats and mice. Following administration of up to 1000 mg/kg/day BC extract by gavage for 90 days, dose‐related increases in micronucleated peripheral blood eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…With the aim of standardization, several lines of research are being developed to provide tools for the scientific validation of these products of natural origin to improve the treatment of infectious diseases and metabolic disorders 23,24 . Many medicinal plants and natural products, although having therapeutic properties, have shown pronounced toxicity at a certain dose 14 . Therefore, determining lethal doses or concentrations and toxicological parameters is essential to guarantee the safety of using these natural products 25 .…”
Section: Evolution Of Biochemical and Hematologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of standardization, several lines of research are being developed to provide tools for the scientific validation of these products of natural origin to improve the treatment of infectious diseases and metabolic disorders 23,24 . Many medicinal plants and natural products, although having therapeutic properties, have shown pronounced toxicity at a certain dose 14 . Therefore, determining lethal doses or concentrations and toxicological parameters is essential to guarantee the safety of using these natural products 25 .…”
Section: Evolution Of Biochemical and Hematologicalmentioning
confidence: 99%
“…The preparations of medicinal plants contain hundreds of compounds that can have antioxidant, antihypertensive, vasorelaxant, immunostimulant, immunosuppressive, antiinflammatory, antibacterial, antiviral, and antiparasitic properties [11][12][13] . Although considered safe, some natural compounds can be toxic to the body because any biologically active compound can be toxic depending on the dose 14,15 . Numerous studies have reported cases of toxicity due to the abuse of plant-based preparations.…”
mentioning
confidence: 99%